The impact of intergenerational support on multidimensional poverty in old age: empirical analysis based on 2018 CLHLS data - Tan, Hong; Dong, Zhihua; Zhang, Haomiao (Humanities & social sciences communications, 2023)
Intergenerational support from children and differences in social security treatment are important factors influencing the occurrence of multidimensional poverty among the elderly in China. Drawing on social support theory, based on the data of the 2018 Chinese Longitudinal Healthy Longevity Survey, this article investigates the effects of different intergenerational support provided by children on multidimensional poverty among the elderly, using a combination of logit regression model and moderating effect model, and identify the role played by social security programs. The study shows that multidimensional poverty among the elderly in China is generally severe, and the structure of poverty is evolving from material to spiritual poverty. The effectiveness of financial and caregiving support in the management of multidimensional poverty among the elderly has diminished and is limited to rights-based poverty, and the effects are in opposite directions. Emotional support assumes an increasingly important role in poverty management and has a significant impact on the alleviation of economic, health, and spiritual poverty as well as overall multidimensional poverty. Social security programmes have significant moderating effects on the relationship between financial support, emotional support and multidimensional poverty among the elderly, and differences in social security programmes can cause changes in the impact of intergenerational support on multidimensional poverty among the elderly. This study has theoretical value and practical implications for building a solid bottom line for a mass return to poverty and improving the current situation of multidimensional poverty among the elderly in China.